Case Report: Laparoscopic resection of a tumor in the right posterior lobe of the liver in a patient with situs inversus totalis - Yang, Bin; Luo, Xin; Mao, Genjun (Frontiers in Oncology, 2025)
BackgroundLiver cancer poses a major health burden worldwide. Therefore, surgical resection is an important treatment option for patients with liver cancer. In situs inversus totalis (SIT), a rare genetic condition, organs such as the heart, liver, spleen, and stomach are unpaired in the chest and abdominal cavity and their positions are opposite their usual positions.Case presentationWe report a case of SIT with a tumor in the right posterior lobe of the liver in a 70-year-old man. This patient was successfully treated with laparoscopic resection.ConclusionsThis case emphasizes that laparoscopic hepatectomy, comprising comprehensive preoperative preparation and fine intraoperative cooperation, is safe and feasible in patients with SIT.